Description of Citizens Intrinsic Motivation for Participating Skill Education Program of PKK - Hafifah Mega Sari; Ismaniar Ismaniar (Universitas Negeri Padang, 2019)
This research was motivated by the high enthusiasm of the people in participating in the PKK program skills training program in Sungai Pasak Village. This is allegedly due to the intrinsic motivation of the citizens when participating in skills training. This type of research is quantitative descriptive research. The population in this study were citizens who participated in activities PKK skills a 25 people. The sample in the study amounted to 20 people. The results showed that the intrinsic motivation of citizens in participating in educational activities and skills of the family welfare empowerment program in Sungai Pasak Village, District of East Pariaman, was seen from the level of physiological needs, social needs, the need for appreciation, self-actualization needs, high category. Suggestions to PKK institutions to continue hold community programs that fit their needs.Keywords: Skill Education Program, Citizens, Intrinsic Motivation